The Reverend Jim Jones and Religious, Political, and Racial Radicalism in Peoples Temple - (:unkn) unknown (My University, 2015)
On November 18, 1978 over 900 members of Peoples Temple committed suicide or were murdered in Jonestown, Guyana under the direction of Reverend Jim Jones. This thesis explores the radical ideology of Jones leading up to and including the day of the murder-suicides by poisoned Flavor-Aid. Jones was a radical theologically, politically, and in racial thinking, although he was not an advocate for women’s rights. Jones claimed to be a prophet and then God, criticized the Bible and became atheistic, called himself a Marxist, a socialist, and a Communist, and strove for equal rights for minorities in the United States through his interactions with the Black Panther Party and prominent black religious figures, including Father Divine. The “cult” was said to have committed “revolutionary suicide,” a phrase used by Huey Newton. Jones’ radicalism in Peoples Temple may be one factor that ultimately led to the destruction of Jonestown that day.
Keywords: Cult; Jim Jones; Jonestown; Mass Suicide; Peoples Temple; Religion